A phase II, single center, randomized, double‐blind, placebo‐controlled study of the safety and therapeutic effectiveness of intranasal glulisine in amnestic mild cognitive impairment and probable mild Alzheimer's disease: Human/Human trials: Other. (7th December 2020) - Rosenbloom, Michael H.; Barclay, Terry R; Erickson, Lauren O; Pyle, Maria; Green, Emily A.; Svitak, Aleta; Hage, Lyndsay M.; Frey, William H.; Hanson, Leah R.
Abstract: Background: IN insulin is a potential treatment for neurodegenerative disease shown to increase cerebral glucose update, reduce amyloid plaques and improve verbal memory in cognitively‐impaired as well as normal adults. Investigations have suggested that rapid‐acting (RA) insulins such as glulisine may result in superior cognitive benefits compared to regular insulin. Method: We performed a single center, randomized, double‐blind, placebo‐controlled study to evaluate the efficacy of IN glulisine versus placebo in N=35 memory impaired (MCI/AD) subjects. Subjects with non‐insulin dependent diabetes mellitus (NIDDM) were included in the study. IN administration utilized the Impel NeuroPharma I109 Precision Olfactory Delivery (POD®) device. The ADAS‐Cog13, CDR global score, and FAQ were measured at baseline, 3, and 6 months. Secondary outcome measures included digit span forward/backwards, Trailmaking part A/B, COWAT, and WMS logical memory. Depression and suicidality were assessed using the GDS and C‐SSRS Results: Subjects in the saline group were significantly older than those in the saline group (p=0.022). No significant differences in gender, education, ApoE4 status, and MOCA score existed between treatment groups. Overall, the number of adverse events per person was similar between groups (2.32 vs. 2.24, p=0.824); although subjects receiving IN glulisine had higher rates of nasal irritation (25.0% vs 13.9%) and respiratory symptoms (15.9% vs 8.3%) compared to placebo. Glucose<70 was observed in one subject receiving RA insulin, but otherwise, there were no other cases of hypoglycemia, including three NIDDM patients. Insulin levels and blood pressure was unaffected by treatment. No significant difference for ADAS‐Cog 13, CDR‐SOB or FAQ scores were found between treatment groups at 3 and 6 months. There was no impact of IN glulisine on depression or suicidality. Conclusion: IN glulisine was safe and well‐tolerated and did not consistently impact peripheral glucose or insulin levels. There were no enhancing effects of IN glulisine on cognition, function, or mood, but the ability to detect significance was limited by number of subjects successfully enrolled and study duration. Additional investigations following a larger MCI/AD cohort inclusive of NIDDM subjects over a longer duration are necessary to better evaluate RA insulin efficacy in this population.